Room‐temperature multiferroicity in NiFe2O4 and its magnetoelectric coupling intensified through defect engineering. Issue 12 (21st July 2021) - Cho, Jae‐Hyeon; Cho, Seongwoo; Lee, Jun Han; Palneedi, Haribabu; Lee, Ju‐Hyeon; Kim, Hwang‐Pill; Lee, Nyun Jong; Tigunta, Siriporn; Pojprapai, Soodkhet; Kim, Sanghoon; Ryu, Jungho; Oh, Yoon Seok; et al.
Abstract: The well‐known ferromagnetic oxide, NiFe2 O4, was studied as a potential candidate for room‐temperature Type II magnetoelectrics. A spin canting as one of the essential requirements for Type II multiferroics was induced by breaking the stoichiometry, that is, intentionally subtracting Fe ions. We observed that Fe ions were first subtracted exclusively from the tetrahedral sites, leading to an increase in the magnetoelectric coupling owing to an increasing degree of spin canting. The enhancement in the magnetoelectric coupling culminated beyond the subtraction level of 30 at.%, at which Fe ions started to be removed from the octahedral sites. Alongside, we observed that the subtraction of Fe ions gives rise to a ferroelectricity due to the formation of defect complexes that establish an internal bias field.